2016
DOI: 10.1371/journal.pone.0149347
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging after Completion of Neoadjuvant Chemotherapy Can Accurately Discriminate between No Residual Carcinoma and Residual Ductal Carcinoma In Situ in Patients with Triple-Negative Breast Cancer

Abstract: BackgroundThe accurate evaluation of favorable response to neoadjuvant chemotherapy (NCT) is critical to determine the extent of surgery. We investigated independent clinicopathological and radiological predictors to discriminate no residual carcinoma (ypT0) from residual ductal carcinoma in situ (ypTis) in breast cancer patients who received NCT.Patients and MethodsParameters of 117 patients attaining pathological complete response (CR) in the breast after NCT between January 2010 and December 2013 were retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…On MRI, the in situ component can present as a non‐mass enhancement. Of 117 patients with TNBC studied by Park et al ,. 67 had ypT0 and 50 ypTis disease after breast surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On MRI, the in situ component can present as a non‐mass enhancement. Of 117 patients with TNBC studied by Park et al ,. 67 had ypT0 and 50 ypTis disease after breast surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression analysis has revealed that TNBC comprises a heterogeneous group of tumours. Multiple studies have shown that TNBC is more sensitive to neoadjuvant chemotherapy (NACT) than other molecular subtypes, with pathological complete response (pCR) rates of up to 50 per cent. Although TNBC is associated with poor prognosis, with high rates of metastasis and short relapse‐free survival, patients who achieve a pCR on NACT have improved survival and fewer locoregional recurrences than patients with residual disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…67 Furthermore, MRI may be essential in evaluating axillary lymph node involvement in breast cancer treatments, 68 and in identification of residual ductal carcinoma in situ following NAT. 45,69 One limitation of the quantitative MRI techniques currently available is that there are no multi-site, multi-vendor studies presently validating them. 27 …”
Section: Emerging Strategiesmentioning
confidence: 99%
“…Nevertheless, our results add to the evidence that, post‐neoadjuvant therapy, MRI is likely more useful for predicting pCR in HER2‐positive tumours, with PPV 100% in this subgroup. Recent evidence also indicates that MRI has higher accuracy with regards to TNBC, but this was not seen in our analysis . This is likely a reflection of the small numbers in our subgroups, but examination of the individual cases also underlines the limitations of MRI in detecting microscopic residual disease.…”
Section: Discussionmentioning
confidence: 59%